Assessment of the Diagnostic Value of Plasma Levels, Activities, and Their Ratios of von Willebrand Factor and ADAMTS13 in Patients with Cerebral Infarction. (April 2016) - Qu, Le; Jiang, Miao; Qiu, Wenjuan; Lu, Shiqi; Zhao, Yunxiao; Xia, Lijun; Ruan, Changgeng; Zhao, Yiming
Background and Objectives: Raised levels of von Willebrand factor (VWF) and reduced levels of a disintegrin and a metalloproteinase with a thrombospondin type I motif, member 13 (ADAMTS13) activity are associated with thrombosis. We aimed to investigate the relationships between plasma levels of VWF and ADAMTS13, their ratios, and the occurrence of cerebral infarction and to understand the roles of VWF and ADAMTS13 in cerebral infarction. Methods: Ninety-four patients with cerebral infarction and 103 controls were analyzed. Plasma levels of VWF antigen (VWF: Ag), VWF ristocetin cofactor activity (VWF: Rcof), and VWF collagen binding activity (VWF: CB) were measured by enzyme-linked immunosorbent assay (ELISA). The ADAMTS13 activity (ADAMTS13) was measured with FRETS-VWF73. The relationship between plasma levels and ratios of VWF and ADAMTS13 and the occurrence of cerebral infarction were analyzed. Results: Patients with cerebral infarction displayed higher VWF: Ag and VWF: Rcof levels and lower ADAMTS13, VWF: CB/VWF: Ag, ADAMTS13/VWF: Ag, and ADAMTS13/VWF: Rcof levels compared to controls ( P < .01). The highest quartiles of VWF: Ag (odds ratio [OR] = 5.11, 95% confidence interval [CI], 1.49-17.50) and VWF: Rcof (OR = 5.04, 95% CI, 1.62-15.66) and the lowest quartiles of VWF: CB/VWF: Ag (OR = 5.91, 95% CI, 1.95-17.93), ADAMTS13/VWF: Ag (OR = 9.11, 95% CI, 2.49-33.33), and ADAMTS13/VWF: Rcof (OR = 3.73, 95% CI, 1.39-10.03) are associated with cerebral infarction. Conclusions: An association was found between reduced levels of VWF: CB/VWF: Ag, ADAMTS13/VWF: Ag, and ADAMTS13/VWF: Rcof ratios and cerebral infarction. Our data suggest that increased levels of VWF and reduced levels of ADAMTS13 activity may contribute to the pathogenesis of cerebral infarction.